Mathematical knowledge in early school grades: advanced mathematics from an elementary point of view? - Wagner Rodrigues Valente (Acta Scientiarum. Education, 2015)
This text aims to discuss the mathematics of early school years from a historical perspective. Supported on recent research results derived from projects implemented through national and international cooperation, the work to be published analyzes the difficulties of conducting historical studies about the presence of mathematics in the initial training of students. Said difficulties include the way to treat the types of mathematical teaching in the form of subjects rather than discipline-like contents. This implies a special attention to the articulation that occurs between pedagogies and pieces of knowledge to be taught. Additionally, this case requires the analysis of the cultural purposes in each school time, and of the role of mathematical knowledge. Among the findings of the study, there is an evident watershed with the emergence of modern pedagogies in the last decades of the 19th century and first decades of the 20th century, and the redefinition of mathematical basics.